Works Of Rukn Al-Din Ubaydullah As-Samarqandi on Fiqh and Usul Al-Fiqh - Sunnatulla Abdullaev (Indonesian Journal Publisher, 2025)
This article examines the scholarly legacy of Rukn al-Din Ubayd Allah as-Samarqandi, a prominent scholar who lived and worked in the intellectual milieu of Transoxiana in the 7th/13th century. Special attention is given to his major work Jāmiʿ al-uṣūl fī bayān al-qawāʿid al-ḥanafiyya wa ash-shāfiʿiyya fī uṣūl al-fiqh, which systematically compares and organizes the methodological principles of the Hanafi and Shafi‘i schools. The study also considers his other works, including Talkhīṣ Jāmiʿ al-uṣūl, Risāla fī ḥurūf al-maʿānī, Mulakhkhaṣ min Sharḥ maʿānī al-āthār, Risāla fī al-qawāʿid al-fiqhiyya, Tafsīr gharāʾib maʿānī al-Qurʾān, and Iʿjāz al-Qurʾān. The analysis highlights their intellectual foundations, referencing influential scholars such as al-Pazdawī, as-Sarakhsī, al-Māturīdī, al-Jaṣṣāṣ, ad-Dabūsī, and al-Ghazālī, and notes the current locations of the manuscripts (Süleymaniye Library in Istanbul and Dār al-Kutub al-Miṣriyya in Cairo). The research underscores the concise, didactic, and comparative nature of Samarqandi’s works and their significance within the Māturīdī intellectual tradition.